TRANSFORMASI HUKUM KELUARGA ISLAM DI INDONESIA: ANTARA NORMA SYARIAH DAN DINAMIKA SOSIAL KONTEMPORER - Muhammad Adieb (CV. ADIBA AISHA AMIRA, 2025)
Islamic family law is a critical branch of Islamic jurisprudence that closely relates to the social life of Muslim communities. It encompasses matters such as marriage, divorce, spousal rights and obligations, guardianship, inheritance, and child custody. As social and cultural dynamics evolve, there is an urgent need for a methodological response to ensure that Islamic family law remains relevant and beneficial. This article explores the dynamics of Islamic family law between textual norms and social contexts. Using a normative-legal and sociological approach, this study examines the application of Islamic family law in Indonesia within the framework of maqāṣid al-sharī‘ah, highlighting contemporary issues such as child marriage, polygamy, unilateral divorce, and women's rights. The findings suggest that strengthening the role of religious court judges, enhancing public education, and reinterpreting Islamic law through a gender-justice lens are key to reforming Islamic family law in an era of change.